The Research University in Brazil: 1930 and 2030 - Pedrosa, Renato H.L. (International Higher Education, 2014)
Brazil’s higher education system developed quite late—and the first research university was established in the 1930s. This article discusses the origins of Brazil’s research system and the current developments and challenges facing research universities.